Governance, Management, and Accountability in Secondary Education in Sub-Saharan Africa - World Bank (Washington, DC : World Bank, 2012)
The purpose of this study, educations for all has led to a significant increase in the number of students completing primary education in Sub-Saharan Africa (SSA). It has also created tremendous demand for secondary education. This paper discusses the processes that support upward and downward accountability in the secondary education system and processes designed to ensure internal accountability and accountability for learning outcomes. This report focuses on school-level management as the place where governance structures and management processes converge. It examines the role of various governance structures for secondary schools and their impact on the management of teachers and of general academic and financial management. Finally this publication summarizes the discussions in terms of the key issues and suggestions for improvements within educational governance, management, and accountability.